Vascular trauma and haemorrhage after firearm injuries - Karolina Karlsson Nyberger (2025)
Firearm injuries are an increasing global health problem resulting in deaths and disabilities among its victims as well as an immense burden both for the society as well as the health care system. Vascular injuries and haemorrhage are particularly lethal after gun violence. The aim of this thesis was to investigate management strategies and patient outcomes of vascular injuries and haemorrhage after firearm injuries.Paper I was a systematic review characterising injuries and mortality after CPMSs focusing on in-hospital management of haemorrhage and vascular injuries. The paper showed an overall high mortality after CPMSs with injuries mainly located to the extremities (35%), abdomen (20%) and thorax (19%) with approximately one quarter of deaths being related to haemorrhage involving central large vessel injuries. 47% (97/206) of all hospitalised patients required a surgical procedure.Paper II was a retrospective nationwide epidemiological study including all patients with firearm injuries between 2011 and 2019 (n=1010). The most common injury location was lower extremity (30%) followed by upper extremity (14%), abdomen (14%), and thorax (13%). The head was the most severely injured body region. It showed an annual increase of firearm-related injuries and fatalities (P